2021
DOI: 10.1038/s41467-021-26600-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide profiling in colorectal cancer identifies PHF19 and TBC1D16 as oncogenic super enhancers

Abstract: Colorectal cancer is one of the most common cancers in the world. Although genomic mutations and single nucleotide polymorphisms have been extensively studied, the epigenomic status in colorectal cancer patient tissues remains elusive. Here, together with genomic and transcriptomic analysis, we use ChIP-Seq to profile active enhancers at the genome wide level in colorectal cancer paired patient tissues (tumor and adjacent tissues from the same patients). In total, we sequence 73 pairs of colorectal cancer tiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 51 publications
0
47
0
Order By: Relevance
“…Summarizing the recent studies in multiple cancers [4][5][6][7][8][9][10][11] (Table 1), we distilled a bioinformatics workflow for the identification of subtype-specific SEs and putative targets with multi-omics characterizations, followed by SE-driven regulatory network inference to dissect cancer heterogeneity and elucidate the transcriptional circuitry underlying specific cancer subtypes (Figure 1).…”
Section: A Bioinformatics Workflow For Interrogating Se Heterogeneitymentioning
confidence: 99%
“…Summarizing the recent studies in multiple cancers [4][5][6][7][8][9][10][11] (Table 1), we distilled a bioinformatics workflow for the identification of subtype-specific SEs and putative targets with multi-omics characterizations, followed by SE-driven regulatory network inference to dissect cancer heterogeneity and elucidate the transcriptional circuitry underlying specific cancer subtypes (Figure 1).…”
Section: A Bioinformatics Workflow For Interrogating Se Heterogeneitymentioning
confidence: 99%
“…Here, aiming to investigate dMRR and MSI-related signature in somatic mutations called by RNAseq, we tried to extend the application of GSGP to transcriptome MSs. Firstly, we collected RNAseq data from two CRC cohorts, Chonnam National University and Pusan National University CRC (CP-CRC) 45 and Zhongnan Hospital CRC (ZN-CRC) 46 , which contain 45 and 72 pairs of tumor-normal paired samples, respectively. When using a priori SBS signatures, we found that neither our identified SBS54 nor the widely established 7 dMMR-related signatures can distinguish between MSI and MSS samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two CRC RNAseq datasets were downloaded from the Sequence Read Archive (SRA) (https://ncbi.nlm.nih.gov/sra) with accession number PRJNA748264 45 (n=45) and PRJNA658001 46 (n=72). SRA Toolkit (v3.0.0) was used to split the SRA files into pair-end FASTQ files.…”
Section: Methodsmentioning
confidence: 99%
“…Super-enhancer was found to activate the Wnt/beta-catenin pathway and promotes the proliferation of liver cancer cells [ 17 ]. Oncogenic super-enhancers were also identified in colorectal cancer through genome-wide profiling [ 18 ]. In addition, super-enhancer was reported to play a role in glioma progression [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma specimens, a live-specific super-enhancer drives lncRNA-DAW, leading to activation of the Wnt/beta-catenin pathway. Oncogenic super-enhancers were also identified in colorectal cancer through genome-wide profiling [ 18 ]. Via a genome-wide investigation of the enhancer distribution in colorectal cancer tissues, super-enhancer loci were identified.…”
Section: Introductionmentioning
confidence: 99%